1997
DOI: 10.1007/bf01294720
|View full text |Cite
|
Sign up to set email alerts
|

Glycine and D-serine decrease MK-801-induced hyperactivity in mice

Abstract: It is well known that the un-competitive N-methyl-D-aspartate (NMDA) receptor antagonist phencyclidine can induce a syndrome in humans that mimics both positive and negative symptoms of schizophrenia. In the light of this observation, it has been hypothesised that schizophrenia might be due to a hypofunction of central glutamate systems. A glycine agonist, by strengthening glutamatergic transmission, has been suggested to be useful as treatment. A crucial issue is the uncertainty regarding the degree of satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 31 publications
4
29
0
Order By: Relevance
“…Hence, development of NMDA receptor antagonists for therapeutic use in PD has been pursued actively during the past few years. But these glutamate antagonists have very low effectiveness, and a plethora of side effects that have limited their clinical utility as neuroprotectants (Sonsalla et al, 1992;Engber et al, 1994;Nilsson et al, 1997;Li et al, 2002). An alternate strategy is to attenuate the excitotoxic response in the basal ganglia by indirectly modulating other interacting neurotransmitter systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, development of NMDA receptor antagonists for therapeutic use in PD has been pursued actively during the past few years. But these glutamate antagonists have very low effectiveness, and a plethora of side effects that have limited their clinical utility as neuroprotectants (Sonsalla et al, 1992;Engber et al, 1994;Nilsson et al, 1997;Li et al, 2002). An alternate strategy is to attenuate the excitotoxic response in the basal ganglia by indirectly modulating other interacting neurotransmitter systems.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate binds to a variety of excitatory amino acid receptors, especially the NMDA receptor, leading to prolonged and excessive depolarization and neuronal activation resulting in the death of target neurons (Choi, 1988;Lynch and Dawson, 1994). Consequently, NMDA receptor blockade in PD research has been actively pursued over the past decade, but to date has been limited by the side effects of the glutamate antagonists (Nilsson et al, 1997;Li et al, 2002) and their mixed effectiveness (Sonsalla et al, 1992;Engber et al, 1994).…”
mentioning
confidence: 99%
“…Both glycine Toth and Lajtha, 1986) and D-serine (Contreras, 1990;Nilsson et al, 1997) have been shown to reverse the behavioral effects of PCP in rodents following acute administration, indicating the in vivo relevance of the interaction. The effects of these agents during long-term administration, however, have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, NMDA receptor antagonist-treated animals have been widely used as models of schizophrenia (Noda et al, 1995;Sams-Dodd, 1996;Nilsson et al, 1997;Enomoto et al, 2005Enomoto et al, , 2007. To evaluate the effects of TAK-063 on spatial working memory deficits produced by an NMDA receptor antagonist, the Y-maze test and radial arm maze task were used (Lalonde, 2002;Hughes, 2004;AbdulMonim et al, 2006).…”
Section: Discussionmentioning
confidence: 99%